SALURAN PEMASARAN LANGSUNG JASA PERIKLANAN MEDIA LUAR RUANG PT WARNA WARNI MEDIA - Ratih Setyo Rini; Faizal Roni; Belinda Putri Maharani (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Direct marketing is one form of marketing that companies choose to be able to reach potential clients more quickly. This study describes the Direct Marketing Strategy of Outdoor Media Advertising Services at PT Warna Warni Media Jakarta. The research was conducted from February to April 2017 using qualitative research methods. PT Warna Warni Media, as a company engaged in outdoor media advertising services, markets its products directly. PT Warna Warni Media Jakarta has two direct marketing channels in marketing the company's products, namely through face-to-face contact with an Account Executive assisted by direct mail by Marketing Support. Over the past three months, the Direct Marketing Team has succeeded in closing deals 67 times out of 132 negotiations that have been conducted. The success of the company's direct marketing cannot be separated from the form of promotion it provides, in the form of discount, bartering and sponsorship programs